Eksplorasi Etnomatematika Pada Gerabah Mlaten - Isnaindah Jasmine Pertiwi; Mega Teguh Budiarto (Mathematics Education Study Program, 2020)
Abstract Culture is used as a means to learn from everyday life. Mathematics can be associated with daily life, which can be learned through culture. The term mathematics in culture is called ethnomatematics. Each region has its own culture. In the village of Mlaten there is also a legacy that has been passed down, namely pottery with typical Majapahit carvings. The purpose of this study is to explore the mathematical concepts contained in the Mlaten pottery, so that they can be used as learning resources in learning mathematics. Through the study of literature, exploration, and observation, as well as by an ethnographic approach, it can be concluded that the mathematical concepts contained in the Mlaten earthenware are the concept of a circle, the concept of geometry transformation, the concept of flat shape, the concept of curved side space, the concept of function, and the concept of volume rotating objects. Ethnomatematics can make it easier for students to understand everyday problems. Keyword: Ethnomathematics, Mathematicals concepts, Pottery Abstrak Budaya dijadikan sebagai sarana untuk belajar dari kehidupan sehari-hari. Matematika dapat dikaitkan dengan kehidupan sehari-hari, yaitu dapat dipelajari melalui budaya. Istilah matematika dalam budaya disebut dengan etnomatematika. Setiap daerah memiliki budaya masing-masing. Di desa Mlaten juga ada warisan yang sudah turun temurun yaitu gerabah dengan ukiran khas Majapahit. Tujuan penelitian ini adalah untuk mengeksplorasi konsep matematika yang terdapat pada gerabah Mlaten, sehingga dapat dijadikan sumber belajar dalam pembelajaran metematika. Melalui studi literatur, eksplorasi, dan observasi, serta dengan dilakukan pendekatan etnografi, maka dapat disimpulkan bahwa konsep matematika yang terdapat pada gerabah Mlaten adalah konsep lingkaran, konsep transformasi geometri, konsep bangun datar, konsep bangun ruang sisi lengkung, konsep fungsi, dan konsep volume benda putar. Etnomatematika dapat mempermudah siswa memahami permasalahan sehari-hari. Kata kunci : Etnomatematika, Konsep Matematika, Gerabah